Moral Education in Strengthening Teachers' Spiritual Values from The Perspective of The Qodiriyah Wa Naqsabandiyah Tarekat - Lutfi, Muhammad Khoirul; Maimun, Agus; Padil, Moh.; Barizi, Ahmad; Masuwd, Mowafg Abrahem (Jurnal al-Thullab, 2025)
This investigates moral education through spiritual reinforcement of teachers in the Qodiriyah wa Naqsyabandiyah Tarekat at MA Darul Ulum Karangpandan, Pasuruan, addressing contemporary moral degradation in formal education. Employing qualitative case study methodology with triangulated data collection, the research is grounded in the theo-anthropocentric paradigm and Islamic intellectual traditions. Three principal findings emerged. First, "kun ma'a man ma'allah" constitutes the conceptual framework, operationalized through tazkiyah al-nafs, istiqāmah, muḥāsabah, and divine love. Second, implementation occurs through dual approaches: value internalization via takhallī and taḥallī strategies incorporating bay'ah, riyāḍah, tawajjuhān, and qudwah; and institutional integration through religious activities and performance appraisal systems. Third, implications manifest in teachers' spiritual transformation encompassing ma'rifatullāh, al-wa'y al-ilāhī, and takhalluq bi akhlāq Allāh. The study demonstrates how Sufistic moral education cultivates ethical consciousness among educators within formal educational contexts.